Analysis of the Impact of the Covid-19 Pandemic on the Fiscal Health of Regency / City in West Sumatra Province - Suci Anggreini Novi; Suhairi Suhairi (Jurnal Mantik, 2023)
This study aims to determine the level of fiscal health before and during the covid-19 pandemic and analyze the factors that affect the fiscal health of the Regency or City Government in West Sumatra Province. Data collection was taken from the District or City Financial Statements in West Sumatra Province in 2019-2020. The entire population in this study was sampled so that 19 Financial Statements were obtained. Comparative analysis is used as a technique in conducting analysis and testing hypotheses. The results of this study indicate a significant difference in 2018-2019 before covid-19 occurred with 2020-2021 when covid-19 occurred. At the time before covid-19 occurred, there were 3 districts or cities in the good category, 16 others in the sufficient category, but during the covid-19 pandemic, all districts or cities were in the sufficient category.